Digital Tools for Management of Innovative Activities of Tourism Enterprises: Ukrainian Analysis of Wartime Challenges - Yakуmenko-Tereshchenko, Nataliia; Kiziun, Alla; Hrabar, Maryna; Brytvienko, Anastasiia; Medvid, Larysa (Canadian Institute for Knowledge Development, 2023)
The article aims to analyse digital tools for managing the tourism enterprises' innovative activities based on the Ukrainian experience of overcoming the risks of martial law. The novelty of the research consists in determining the possibilities of digital management in war conditions, which is an extremely important experience for European countries that never faced such a crisis. In order to gain a comprehensive understanding of the integration of digital tools in Ukraine's tourism industry, statistical data obtained from over 200 enterprises were analysed. This data leveraging enabled the identification of the key management practices that were implemented during the COVID-19 pandemic and subsequently adapted to the martial law restrictions. An interdisciplinary methodological toolkit was used in order to conduct the research: analysis, synthesis, induction, deduction, and comparison. The results demonstrated modern digital tools for managing tourist activities based on consideration of the world and Ukrainian contexts. Special emphasis was also placed on the development of leadership as a phenomenon capable of improving the perception of innovations and appropriate management decisions against the general implementation of modern management methods. The conclusions showed the capabilities of information systems, multimedia databases, and customer relationship management software. It is also important to emphasise the role of digital tools in the tourism industry of Ukraine and their use as a response to the military challenge. Consequently, the importance of targeted advertising and the widespread use of mobile devices is evident. In martial law conditions, they are an important answer to modern problems.
Keywords: digitalization; management; innovation; tourism; enterprises